Modern Percutaneous Hallux Valgus Surgery for Revision of Recurrent Hallux Valgus - Andreas Kurt Toepfer MD PhD; Pawel Chomej MD; Pablo Mococain MD; Henryk Liszka MD PhD; Robbie Ray MBChB, ChM(TO), FRCSed(Tr&Orth), FEBOT; Tom Lewis MBChB (Hons) BSc. (Hons) MFSTEd FRCS(Tr&Orth); Peter Lam MBBS (Hons), FRACS, FAOA; David Gordon MB ChB, MRCS, MD, FRCS (Tr&Orth) (Foot & Ankle Orthopaedics)
Category: Bunion; Other Introduction/Purpose: Hallux valgus is the most common foot deformity, and recurrent deformity is the most common complication after primary hallux valgus correction. The principles of HV revision surgery do not differ from the initial goal of hallux valgus correction, which is to restore physiologic alignment and alleviate symptoms. Choosing the appropriate procedure to address the given deformity pattern and the technical competence to perform the corrective procedure are the keys to success. To date, no 3rd or 4th generation minimally-invasive technique for the correction of recurrent hallux valgus has been described in the literature. The aim of this multicenter analysis is to evaluate the use of modern percutaneous bunion surgery techniques in the revision of recurrent hallux valgus. Methods: A total of 100 cases operated between 2013 and 2023 and contributed by 7 surgeons from 6 countries, all performing percutaneous 3rd and 4th generation Minimally-Invasive Chevron Akin (MICA) / Percutaneous Chevron Akin (PECA) / Minimally Invasive Extra-articular Transverse and Akin (META), were retrospectively evaluated. Minimum follow-up was 12 months (range 12-104). Radiological correction (HVA, IMA, tibial sesamoid position), surgery associated complications using the modified Clavien-Dindo-Sink classification and functional outcome (MOXFQ) were evaluated. Results: The complication rate was 21%. Most complications could be managed non-surgically. The most common complication was screw prominence leading to revision surgery with hardware removal in 8.5% of all cases. Major complications such as deep infection requiring revision surgery were extremely rare. HVA was corrected from a mean of 33.5° to 10.3° at 6 weeks and 9.0° at 12 months, IMA from a mean of 13.9° to 4.8° and 5.1°, respectively. The mean Clapham-Hardy tibial sesamoid position was classified as type 6 preoperatively and improved to type 2 postoperatively. PROMs using the MOXFQ score improved from a preoperative index score of 46.0 to 8.9. Conclusion: Modern percutaneous hallux valgus techniques have proven to be a reliable tool in the primary correction of hallux valgus and metatarsus primus varus, aiming to minimize surgical morbidity and maximize surgical efficiency without compromising safety. To date, there have been no reports of these procedures for recurrent hallux valgus. With adequate training and experience, the use of 3rd and 4th generation MICA/PECA/META is a safe procedure for the revision of recurrent hallux valgus resulting in significant improvements in radiographic parameters, functional outcome and patient satisfaction. The rate of relevant complications is not increased compared to traditional open surgical techniques.